2011
DOI: 10.1177/0731684411415140
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the initiation and growth of delamination in composite materials using acoustic emission under quasi-static three-point bending test

Abstract: Control and optimization of machining processes are important issues affecting the development of productivity. Monitoring systems have become indispensable in the evaluation of materials during machining. In this paper, the path toward the delamination-free drilling of glass/epoxy composite material is established using some novel methods based on acoustic emission features. Acoustic emission monitoring with three techniques, sentry function, acoustic emission energy distribution, and acoustic emission count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…As stated by previous studies [27][28][29][30][31][32][33][34][35][36] AE signal generated from each failure mode of laminated composites, such as matrix cracking, debonding and fiber breakage, has its specific ranges of amplitude and duration. Lower duration and amplitude values are related to matrix cracking, while the higher values are linked with fiber breakage.…”
Section: Clustering Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by previous studies [27][28][29][30][31][32][33][34][35][36] AE signal generated from each failure mode of laminated composites, such as matrix cracking, debonding and fiber breakage, has its specific ranges of amplitude and duration. Lower duration and amplitude values are related to matrix cracking, while the higher values are linked with fiber breakage.…”
Section: Clustering Resultsmentioning
confidence: 99%
“…AE signal is a spontaneous transient energy released by different damage sources such as matrix cracking, fiber breakage during the loading [27]. This technique was used to distinguish the failure modes in laminated composite materials and there was a promising applicability of this method [28][29][30][31][32][33][34]. Their results presented a capable applicability of AE parameters for classification of damage mechanisms in laminated composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Successful results have been reported for damage characterization of composite laminates using the AE parameters. Different frequency, energy and amplitude ranges were observed for different damage mechanisms such as fibre breakage, matrix cracking and delamination [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, three dominant damage mechanisms (matrix-cracking, fiber-matrix debonding and fiber breakage) take place during delamination while these different damage mechanisms generate different AE parameters. Additionally, the achieved results specified that higher frequencies and amplitudes emerging in the tests were related to fiber breakage while lower ranges contributed to matrix cracking and fiber-matrix debonding damages [2,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, some researchers discriminated the AE signatures of damage mechanisms in composite materials [7][8][9][10][11][12]. Their results showed that AE technique is a capable tool for characterization of damage mechanisms in thermoplastic and thermoset laminated composite materials.…”
Section: Introductionmentioning
confidence: 99%